2009
DOI: 10.1088/1748-0221/4/07/t07001
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of the CMS silicon strip tracker during stand-alone commissioning

Abstract: The results of the CMS tracker alignment analysis are presented using the data from cosmic tracks, optical survey information, and the laser alignment system at the Tracker Integration Facility at CERN. During several months of operation in the spring and summer of 2007, about five million cosmic track events were collected with a partially active CMS Tracker. This allowed us to perform first alignment of the active silicon modules with the cosmic tracks using three different statistical approaches; validate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…CMS 2008 cosmic ray data LAS (this analysis) LAS (sector test) Survey CMS 2008 cosmic ray data LAS (this analysis) LAS (sector test) Survey Figure 14: The three alignment parameters for positive z TEC disks measured using cosmic ray data (solid blue circles), by the LAS in this analysis (open black circles), during the LAS sector test [9] (red squares), and by optical survey (green triangles): rotation around global z (left) and translation in global x (middle) and in global y (right).…”
Section: Validation With the Laser Alignment Systemmentioning
confidence: 99%
“…CMS 2008 cosmic ray data LAS (this analysis) LAS (sector test) Survey CMS 2008 cosmic ray data LAS (this analysis) LAS (sector test) Survey Figure 14: The three alignment parameters for positive z TEC disks measured using cosmic ray data (solid blue circles), by the LAS in this analysis (open black circles), during the LAS sector test [9] (red squares), and by optical survey (green triangles): rotation around global z (left) and translation in global x (middle) and in global y (right).…”
Section: Validation With the Laser Alignment Systemmentioning
confidence: 99%
“…the particle trajectory cannot be well described without taking them into account in the track model. This is achieved in a rigorous and efficient way as explained below in this section, representing an improvement compared to previous MILLEPEDE II alignment procedures [10,11,13] for the CMS silicon tracker, which ignored correlations induced by multiple scattering.…”
Section: Track Parameterisationmentioning
confidence: 99%
“…The methodology of the tracker alignment in CMS builds on past experience, which was instrumental for the fast start-up of the tracking at the beginning of LHC operations. Following simulation studies [10], the alignment at the tracker integration facility [11] demonstrated the readiness of the alignment framework prior to the installation of the tracker in CMS by aligning a setup with approximately 15% of the silicon modules by using cosmic ray tracks. Before the first proton-proton collisions at the LHC, cosmic ray muons were recorded by CMS in a dedicated run known as "cosmic run at four Tesla" (CRAFT) [12] with the magnetic field at the nominal value.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute alignment of individual silicon modules is performed with cosmic ray muons and tracks from hadron-hadron collisions collected during periods of commissioning or collision data taking [4][5][6]. A significant advance in the track-based alignment came with the introduction of a global χ 2 algorithm that combines reconstruction of the track and alignment parameters [7].…”
Section: Introductionmentioning
confidence: 99%